Comparison the number of bacteria between washing hands using soap and hand sanitizer as a bacteriology learning resource for students - Satya Darmayani; Askrening Askrening; Apita Ariyani (University of Muhammadiyah Malang, 2017)
Hands are the principal carriers of bacterial diseases, therefore very important to know that washing hands with soap or hand sanitizer is highly effective healthy behaviors to reduce bacteria in the palm. This study aimed to determine the total number of bacteria between washing hands with soap and hand sanitizer, also applying the results of these studies as a learning resource in bacteriology. The research design was the true experiment with pretest-posttest control group research design and laboratory examination. Analysis of data using paired t-test and independent sample t-test with α = 0.05. The result using paired t-test obtained t count= 2.48921> t 0.05 (14) = 2.14479 (with liquid soap), obtained t count= 2.32937> t 0.05 (14) = 2.14479 (with hand sanitizer). As for the comparison of the total number of bacteria include washing hands with soap and hand sanitizer using independent samples t-test obtained results there were differences in the total number of bacteria include washing hands with liquid soap and hand sanitizer with t count= 2.23755> t 0.05 ( 13) = 2.16037. That results showed hand sanitizer more effective to reduce the number of bacteria than the liquid soap, that was hand sanitizer 96% and liquid soap by 95%.